The librarian spy eaudiobook A novel of world war ii. - Martin, Madeline (Harlequin Audio, 2022)
A NATIONAL BESTSELLER—for fans of All the Light We Cannot See and The Tattooist of Auschwitz! "Readers will be on the edge of their seats.... A brilliant tale of resistance, courage and ultimately hope." – Kelly Rimmer, New York Times bestselling author of The Warsaw Orphan From the New York Times bestselling author of The Last Bookshop in London comes a moving new novel inspired by the true history of America's library spies of World War II. Ava thought her job as a librarian at the Library of Congress would mean a quiet, routine existence. But an unexpected offer from the US military has brought her to Lisbon with a new mission: posing as a librarian while working undercover as a spy gathering intelligence. Meanwhile, in occupied France, Elaine has begun an apprenticeship at a printing press run by members of the Resistance. It's a job usually reserved for men, but in the war, those rules have been forgotten. Yet she knows that the Nazis are searching for the press and its printer in order to silence them. As the battle in Europe rages, Ava and Elaine find themselves connecting through coded messages and discovering hope in the face of war. "Uplifting, inspiring and suspenseful, this is one to savor!" –Natasha Lester, New York Times bestselling author of The Riviera House "Madeline Martin is a fantastic author. The Librarian Spy is a stunning tour de force of historical fiction." –Karen Robards, author of The Black Swan of Paris Don't miss Madeline Martin's next heartwarming historical novel, The Booklover's Library! Also by Madeline Martin: The Last Bookshop in London The Keeper of Hidden Books